Handbook of Environmental and Ecological Statistics - Gelfand, Alan E., 1945-; Fuentes, Montserrat; Hoeting, Jennifer A. (Jennifer Ann), 1966-; Smith, Richard Lyttleton (Boca Raton, FL : CRC Press, 2017)
"This handbook focuses on the enormous literature applying statistical methodology and modelling to environmental and ecological processes. The statistics community has become increasingly interdisciplinary, bringing a large collection of modern tools to all areas of application in the environmental processes. In addition, the environmental community has substantially increased its scope of data collection including, e.g., observational data, satellite-derived data, and computer model output. The resultant impact in this latter community has been substantial. The contribution of this handbook is to assemble, in roughly 35 chapters, a state-ofthe-art view of this interface"--Provided by publisher.
6.5.1 Modelling environmental heterogeneity -- inhomogeneous Poisson processes and Cox processes
OCLC-licensed vendor bibliographic record.
Keywords: NATURE -- Ecology; SCIENCE -- Environmental Science; Environmental sciences -- Statistical methods; Ecology -- Statistical methods; MATHEMATICS / Probability & Statistics / General; NATURE / Ecology; SCIENCE / Environmental Science